Achieving a low electrical percolation threshold and superior mechanical performance in poly(l-lactide)/thermoplastic polyurethane/carbon nanotubes composites via tailoring phase morphology with the aid of stereocomplex crystallites. Issue 18 (13th February 2017) - Liu, Zhenwei; Bai, Hongwei; Luo, Yuanlin; Zhang, Qin; Fu, Qiang
Abstract : We demonstrate a facile strategy to fabricate highly conductive PLLA/TPU/CNTs composites with very low percolation threshold and good stiffness–toughness balance via constructing stereocomplex crystallites in PLLA melt to tailor phase morphology. Abstract : Selective localization of conductive nanofillers in one phase of co-continuous polymer blends provides an efficient method to greatly reduce the electrical percolation threshold of conductive polymer composites. However, it is still a big challenge to achieve very low percolation thresholds because the critical content for the complete continuity of the selectively filled phase is generally high. In this contribution, taking poly(l -lactide)/thermoplastic polyurethane/carbon nanotubes (PLLA/TPU/CNTs) composite as an example, we demonstrate a facile and versatile strategy for the fabrication of highly conductive PLLA-based composites with very low percolation threshold as well as excellent stiffness–toughness balance via constructing stereocomplex (SC) crystallites in PLLA melt to effectively tailor the phase transition behavior of the blend matrices. To do this, small amounts of poly(d -lactide) (PDLA) capable of co-crystallizing with the PLLA chains to form SC crystallites were incorporated into the composites by melt mixing at 190 °C. These SC crystallites can serve as physical cross-linking points to significantly increase PLLA melt-viscosity and subsequently induce the formation of co-continuous structure in the PLLA/TPU blend matrix at a much lower content of the CNTs-filled TPU phase. As a result, the obtained composites not only show a dramatically reduced percolation threshold (0.3 wt%) but also exhibit a balanced impact toughness and mechanical strength. Importantly, the strategy to promote the complete continuity of the CNTs-filled phase in blend matrix is low-cost and scalable, opening up a new avenue for the design and engineering of highly conductive PLLA-based composites.